(untitled) (REMUNOM, 2026)
The Normative Force of the 1988 Constitution is the central pillar of Brazilian democratic stability, requiring a transition from legal symbolism to practical effectiveness. This study, designed as a theoretical essay based on an integrative literature review, analyzes the application of fundamental rights through the lens of Judicial Decision Engineering. The main objective is to investigate how Konrad Hesse’s "will to constitution" can be operationalized via precedent governance frameworks and data intelligence. The methodology followed the six-stage protocol for integrative reviews, analyzing evidence collected between 2021 and 2026. The results demonstrate that the ineffectiveness of rights stems from an institutional "technical debt," surmountable through the adoption of Hub-and-Spoke models and Legal MLOps practices that ensure the stability of constitutional theses. It is concluded that the competitive advantage of Brazilian constitutionalism lies in transforming the fundamental norm into an ethical, stable, and technologically governed decision system.